2016
DOI: 10.1016/j.cirp.2016.04.131
|View full text |Cite
|
Sign up to set email alerts
|

Effective forming strategy for double-sided incremental forming considering in-plane curvature and tool direction

Abstract: The success of a toolpath in Double-Sided Incremental Forming (DSIF) is strongly related to the specified tool gap. It is hypothesized in this work that maintained contact between tools and the sheet can improve the distribution of sheet thickness and hence, improve material formability and prevent premature fracture. Simulation and experimental studies reveal that thickness prediction models solely dependent on the local wall angle are inadequate for general part geometries. A 'Shamrock' geometry is proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Maximum deviation to the ideal profile can be controlled under 0.4 mm when the correct forming sequence and strategy were applied. Moser et al [57] developed another analogous method corresponding to the in-plane curvature effect. It was observed that the region of loss of contact was affected by the tool motion direction (Fig.…”
Section: Feature-based Toolpath Strategymentioning
confidence: 99%
“…Maximum deviation to the ideal profile can be controlled under 0.4 mm when the correct forming sequence and strategy were applied. Moser et al [57] developed another analogous method corresponding to the in-plane curvature effect. It was observed that the region of loss of contact was affected by the tool motion direction (Fig.…”
Section: Feature-based Toolpath Strategymentioning
confidence: 99%
“…For example, the Two Point Incremental Forming (TPIF) was proposed in which a partial die is utilized to support the material and reduce the undesired global bending and geometric deviation [129]. Based on the TPIF, Double Sided Incremental Forming (DSIF) [145] was proposed to maintain the benefits of the local support while avoiding the overhead costs for the specific die by using a second tool on the opposite side of the metal sheet [128], as shown in Fig. 6.…”
Section: Classification Of Flexibility In Metal Formingmentioning
confidence: 99%
“…DSIF employs two moving tools acting as a forming tool and a supporting tool to increase flexibility and geometric accuracy. Malhotra et al [ 19 ] and Moser et al [ 20 ] studied forming strategies in DSIF to increase formability and geometric accuracy. Praveen et al [ 21 ] compensated the tool paths in DSIF using an analytic model to enhance the geometric accuracy.…”
Section: Introductionmentioning
confidence: 99%